Planejamento e zoneamento ambiental da bacia hidrográfica do manancial Balneário da Amizade nos municípios de Álvares Machado e Presidente Prudente - São Paulo/Brasil - Soares, Fernanda Bomfim [UNESP] (2015)
This work has as main objective to continue the applied research carried out by Soares (2012) in the Fountain Basin Balneario Friendship, located in the municipalities of Alvares Machado and Presidente Prudente, Sao Paulo, Brazil, contributing to the environmental planning and the management plan of this watershed. To this end, it carried out a literature review of theoretical and methodological knowledge of environmental planning, watershed management, water management and landscape geoecology as well as on identifying and analyzing the status of Permanent Preservation Areas (APP) and several environmental laws, among others. The methodology set out the methodological conceptions of Rodriguez (1994), Rodriguez and Silva (2013) and Leal (1995), with the completion of the steps Organization, Inventory, Diagnosis, Prognosis and Propositions, including the elaboration of thematic maps and summary using Geographic Information System (GIS), Global Positioning System (GPS), field work, analysis and systematization of data and information. The importance of this work was due to the experience of discussing an important issue regionally, but also by contact with who got jobs overseas during research internship at the Ludwig-Maximilians-Universitat in Munich, Germany. One hopes that the results and proposals will support the planning and management plan of this watershed by the government and management bodies, including the of Alvares Machado City, the of Presidente Prudente City and the Watershed Committee of Pontal Paranapanema